Aging-friendly design strategies for community public service facilities based on context analysis - Li, Yang; Zhao, Ruolin; Zhang, Xu (Frontiers in Public Health, 2025)
IntroductionAgainst the backdrop of China’s continuously aging population, adapting public service facilities in older urban communities for the older adults has become an important issue in the fields of urban and rural planning and community governance. Most existing studies focus on static functional optimization, ignoring the dynamic needs of the older adults in different situations. This study aims to reveal the dynamic characteristics of the behavioral needs of the older adults in multiple dimensions such as time, space, and social interaction based on the context theory.MethodThrough field investigation and questionnaire analysis, combined with the analytic hierarchy process, we quantify the demand weights of the older adults and semantic judgment methods were introduced as supplementary verification.DiscussionBased on this, we propose strategies such as behavior-oriented flexible facilities, time-responsive light environment regulation, “behavioral overlap area” design for space composite utilization, and data-driven lightweight iterative mechanisms. These provide approaches to aging-friendly renovation that take into account both accuracy and implementability for resource-constrained older communities, addressing the cognitive gap of situational dynamics in traditional designs.